Linear Subspaces in Zeros of Polynomials on Banach Spaces - Verkalets, N.; Zagorodnyuk, A. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
A survey of general results about linear subspaces in zeros of polynomials on real and complex Banach spaces